Effectiveness of Risk Management Implementation at Universiti Selangor (UNISEL) - Ismail, Hashimah; Mat Norman, Mohd Arif (Selangor Humaniora Review, 2021)
Risk can be defined as an obstacle or challenge that can obstruct the ability of effective services to an organisation, especially in relation to the achievement of a set vision and mission. Thus, risk management is an essential strategy for many organisations to improve their performances. Risk management is considered a management tool or strategy to create a better pathway in achieving the organisation objectives by reducing the risk of ineffective processes, losses and damage. Universiti Selangor (UNISEL) has implemented risk management using its own risk management model based on contexts and issues which are derived from the SWOT analysis. All departments and faculties are required to apply this approach in their operations as well as quality objectives which support the university strategic objectives. The achievements of the department's objective qualities are used as the performance indicator to measure the effectiveness of risk control. The model incorporates the risk management of all departments to control the risk of not achieving the university strategic objectives. The likelihood of the risks is monitored and analysed. The effectiveness of the implemented risk management model based on the likelihood trend is presented in this paper. The model proves that the implemented risk management model can minimize the risks of not achieving the organization objectives. In general, it can be concluded that this study is useful and has contributed significant knowledge to better understanding the risk management implementation at UNISEL.